Advanced therapy to cure diabetes: mission impossible is now possible? - Rohban, Rokhsareh; Martins, Christina P.; Esni, Farzad (Frontiers in Cell and Developmental Biology, 2024)
Cell and Gene therapy are referred to as advanced therapies that represent overlapping fields of regenerative medicine. They have similar therapeutic goals such as to modify cellular identity, improve cell function, or fight a disease. These two therapeutic avenues, however, possess major differences. While cell therapy involves introduction of new cells, gene therapy entails introduction or modification of genes. Furthermore, the aim of cell therapy is often to replace, or repair damaged tissue, whereas gene therapy is used typically as a preventive approach. Diabetes mellitus severely affects the quality of life of afflicted individuals and has various side effects including cardiovascular, ophthalmic disorders, and neuropathy while putting enormous economic pressure on both the healthcare system and the patient. In recent years, great effort has been made to develop cutting-edge therapeutic interventions for diabetes treatment, among which cell and gene therapies stand out. This review aims to highlight various cell- and gene-based therapeutic approaches leading to the generation of new insulin-producing cells as a topmost “panacea” for treating diabetes, while deliberately avoiding a detailed molecular description of these approaches. By doing so, we aim to target readers who are new to the field and wish to get a broad helicopter overview of the historical and current trends of cell- and gene-based approaches in β-cell regeneration.